Ferroptosis Contributes to Isoflurane Neurotoxicity - Xia, Yimeng; Sun, Xiaoyun; Luo, Yan; Stary, Creed M. (Frontiers in Molecular Neuroscience, 2019)
Background: The underlying mechanisms of isoflurane neurotoxicity in the developing brain remain unclear. Ferroptosis is a recently characterized form of programmed cell death distinct from apoptosis or autophagy, characterized by iron-dependent reactive oxygen species (ROS) generation secondary to failure of glutathione-dependent antioxidant defenses. In the present study we tested in vitro the hypothesis that ferroptosis contributes to isoflurane neurotoxicity. Methods：Embryonic primary cortical neuronal cultures (day-in-vitro 7, DIV7) were subjected to 2% isoflurane exposure or carrier gas for 6h, with or without pre-treatment with the ferroptosis selective inhibitor ferrostatin-1 (Fer-1). Glutathione peroxidase 4 (GPX4) mRNA and protein expression were assessed by RT-qPCR and immunofluorescent microscopy respectively. Neuronal ROS generation and mitochondrial membrane potential were assessed by live-cell automated fluoroscopy, and cell death by propidium iodide/Hoescht staining. Results: Isoflurane exposure was associated with decreases in transcription and protein expression of the lipid repair enzyme GPX4. Isoflurane resulted in a significant increase in cell death and ROS generation, and significant impairment in mitochondrial membrane potential compared to carrier gas. These effects were ameliorated by Fer-1 pre-treatment. Conclusions: This study demonstrates for the first time that ferroptosis contributes to isoflurane neurotoxicity. Pre-treatment with Fer-1 may be a potential clinical intervention for neuroprotection.